Concentration and Specialization of Economic Activities in the Kingdom of Saudi Arabia - Abdelkader, Salim Bourchid; M'hamed, Hamidouche; Zian, Abderrazak Ahmed (IAIN Surakarta, 2020)
This study presents several indicators for understanding the structure of economic activities in terms of concentration and specialization in the Kingdom of Saudi Arabia. Subsequently, the theoretical description of the different notions of concentration and specialization relating to geographical or sectors aspect is applied to understand the equality in the distribution of wages and employment levels across the country. Thus, the authors have estimated the most important indexes used in a large part of the academic literature and which are most representative of concentration and distribution, such as the Gini, Herfindahl, Theil, Aigiur, and Krugman indexes for the Kingdom of Saudi Arabia during the year of 2017. The sample used in this study consists of four different kinds of firms (very small, small, medium, and large) of twelve sectors of activities and the wages perceived by employees in thirteen administrative areas in the Kingdom of Saudi Arabia. The data are in the forms of annual reports in the year of 2017 obtained from the General Authority for Statistics of Saudi Arabia. The results obtained certainly facilitate the comprehension of the type of income distribution to the active population by sectors and by administrative areas. As for the implication, this study’s results contribute to enrich statistical data and bring added-value to the knowledge that eventually leads to understanding socioeconomic context of the country.